Team Learning from Mistakes: The Contribution of Cooperative Goals and Problem‐Solving* - Tjosvold, Dean; Yu, Zi‐you; Hui, Chun (Journal of Management Studies, 2004)
ABSTRACT Although mistakes may have considerable potential for learning, previous research has emphasized that organizational members are often defensive when their mistakes are pointed out and will even continue with their present course of action despite growing costs. Recent research has shown that team‐level variables, such as psychological safety and shared mental model, can help overcome barriers to learning from mistakes. Structural equation analyses on teams working in a sample of organizations in Shanghai, China, suggested that teams were able to learn from their mistakes to the extent that they took a problem solving orientation. This orientation in turn was based on developing cooperative but not competitive goals within the team. Although competitive and independent goals induce blaming, blaming itself was not significantly related to learning. Blaming, especially when conducted openly, may hold individual team members accountable as well as provoke defensiveness. Findings empirically link the theory of cooperation and competition with the organizational learning literature. Results suggest that cooperative goals and problem solving promote learning from mistakes.